具有抑制血管紧张素酶作用的鼠李糖乳杆菌和用途 (2018)
具有抑制血管紧张素酶作用的鼠李糖乳杆菌和用途，随着相关生物技术、保健医学学科等研究的不断深入，高血压新的生物活性成分、功能基因、功能蛋白等作用新靶点的相继发现，为筛选出高效降压、安全、高活性的益生菌产品提供了基础条件。本发明由采集于自然发酵豆制品中，经分离、纯化、物理诱变、优选获得的高活性菌株，菌学分类名称actobacillus rhamnosus HLH 20120717，菌学特性为：置于37℃恒温培养箱的培养基中进行培养，通过培养发现稀释浓度为10时菌生长较良好，菌落分散；在相同条件下菌落生长有大有小，菌落呈圆形，乳白色，边缘整齐，表面光滑，其中较小的菌落微黄色；保藏号为：CGMCC No.7084。本发明为进步研究开发预防和治疗高血压的益生菌功能性保健食品和药品提供基础。 The invention discloses lactobacillus rhamnosus with an angiotensinase inhibiting function and application of the lactobacillus rhamnosus. With continuous development of study on the correlated biotechnology and the health medicine subject, novel bioactive constituents, functional genes, functional proteins and other novel action targets of hypertension are discovered in succession, so that basic conditions for screening safe and highly active probiotics capable of efficiently lowering blood pressure are provided. The lactobacillus rhamnosus is a highly active bacterial strain collected from a naturally fermented bean product and formed by separation, purification, physi